Metodologi dan Isu-Isu Krusial Tafsir Susastra Bint al-Shāṭi’: Sebuah Penghampiran Singkat - Muhammad Ulinnuha (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2019)
‘Ā’ishah ‘Abd al-Raḥmān bint al-Shāṭi’ (1913-1998) was an Egyptian female scholar who successfully applied a literary approach to interpreting the Qur’an. He put the idea in one of his monumental works, namely al-Tafsīr al-Bayānī li al-Qur’ān al-Karīm. This paper seeks to explain aspects of the interpretation methodology and some of the crucial issues in it. In the aspect of methodology, will be explained about the background of writing, sources, systematics, methods and interpretation patterns. While some crucial issues discussed are about the discourse of synonymity, asbabun nuzul and israiliyat. At the end of this article also comes with some critical notes on the thematic methods offered by Bint al-Shāṭi'’